General response formula for 2-D bilinear systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
Two new models of 2-D bilinear systems are introduced. The general response formulae for the models are derived.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka